EXPERIENCE OF UNDERSTANDING OF THE BIBLICAL NARRATIVE ABOUT THE CREATION OF THE WORLD FROM THE PERSPECTIVE OF MODERN DATA SCIENCE - S. A. Emelyanov (Современная наука и инновации, 2022)
The inconsistency of modern science is particularly evident in situations where it goes beyond its own competence and claims to solve ideological issues that lie in the field of theology and philosophy.